New Automaton-Game Theory Method for Modeling of Reliability and Flexibility Valuation for CAD-CAM Systems - Harbarchuk, V.; Hots, N. (Штучний інтелект, 2011)
The method of reliability and flexibility valuation for computer aided design and flexible manufacture interpreted as
an indivisible purposeful system, which is based on purposeful automaton theory, automaton-game simulation of
design and cluster analyses, developed by the authors, is also investigated herein. The necessity to develop adaptable
self-training systems for the study of these units is grounded. Розглядається новий метод оцінки надійності і гнучкості системи автоматизованого проектування і
виробництва як єдиної цілеспрямованої системи на основі синтезованих автоматно-ігрових моделей,
розроблених авторами, кластерного аналізу і векторних ігр. Рассматривается новый метод оценки надежности и гибкости системы автоматизированного проектирования
и производства как единой целеустремленной системы на основе синтезированных автоматно-игровых
моделей, разработанных авторами, кластерного анализа и векторных игр.